Birds - Ganeri, Anita, 1961- (New York : Gloucester Press, 1993)
Explores the variety and characteristics of birds. Features projects such as making a bird feeder and charting migratory patterns.
What are birds? -- Feathers -- Flight -- Migration -- Bird beaks -- Food and feeding -- Feet -- Night birds -- Bird communication -- Courtship -- Nest building -- Eggs and young -- Where birds live -- The variety of birds.
Includes index and glossary.
Appraisal-Science Books for Young People
6.2
5-8
Keywords: Birds -- Juvenile literature; Birds; Birds